Self-medication Practice among Adults in Lalitpur District - Maharjan, Monika; KC, Tulza (Journal of Nursing and Health Sciences Nepal, 2025)
Introduction: Self-medication is the use of drugs to treat self-diagnosed disorders or symptoms, or the intermittent or continued use of a prescribed medication for chronic or recurrent diseases or symptoms. The objective of this study was to find out the practices of self-medication among adults in a community.Methods: The descriptive cross-sectional study was conducted among 99 adults, selected through a nonprobability convenience sampling technique. Data were collected through in-person interviews using a semi-structured questionnaire. Data analysis was performed using both descriptive and inferential statistics.Results: The study showed that 75.75% of the respondents practiced self-medication. The majority of the respondents practiced self-medication for fever (77.3%), headache (73.3%), and cough and cold (72%). Reasons for self-medication were purchase convenience (77.3%), self-reported minor nature of illness (76%), long queues in clinics (60%), and overcrowding in the hospital (50.7 %).Conclusion: Self-medication is a highly common practice among adults in a Lalitpur District. However, the study found no statistical association between self-medication practice and socio-demographic variables. The findings highlight the necessity of raising public awareness about the potential risks of inappropriate self-medication and promoting safer healthcare-seeking behavior.